A self-assembled nanohelix for white circularly polarized luminescence via chirality and energy transfer. Issue 14 (30th March 2020) - Ma, Sijia; Jiang, Jian; Liu, Zongwen; Jiang, Yuqian; Wu, Zhanpeng; Liu, Minghua
Abstract : Chiral nanostructures and their optical activity have been attracting great interest. Abstract : Chiral nanostructures and their optical activity have been attracting great interest. Here, we designed an enantiomer bolaamphiphile containing a naphthalene moiety (bola-1 ) and an alkyl spacer, and investigated its self-assembly as well as optical activity. It was found that the compound could form gels in various organic or mixed organic/water mixtures. In mixed DMSO/water, it formed a nanohelix. Due to the fluorescent nature of the naphthyl group, the nanohelix showed both CD and circularly polarized luminescence (CPL). When three achiral fluorescent molecules, pyrene-1-carboxylic acid (D2 ), rhodamine 110 (D3 ) and rhodamine B (D4 ), were incorporated into the helical structures formed by bola-1, the nanohelix could be retained and the CPL from the dye molecules could be induced. In addition, an energy transfer occurred between the bola-1 nanohelix and the dyes. By mixing the different emission dyes with the bola-1 in an appropriate ratio, white CPL was obtained. It was found that the dissymmetry factor of the white CPL could be increased through energy transfer. This work provided a new convenient and efficient way for obtaining white CPL.